Information System Design For HSE Awards At PT Wijaya Karya - Faisal, Muhammad Zildan; Utami, Ardhini Warih (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The Health Safety and Environment (HSE) Awards is an appreciation program by PT Wijaya Karya (Persero) Tbk for projects that successfully implement occupational safety, health, and environmental protection standards. The current evaluation process is conducted manually using Microsoft Excel, which is inefficient, time-consuming, and prone to subjective bias, particularly when multiple projects achieve identical scores. This research aims to design and develop a web-based information system to support the evaluation and selection of HSE Awards winners. The Multi-Attribute Utility Theory (MAUT) method was employed because of its effectiveness in handling multiple criteria and heterogeneous sub-criteria, thus ensuring fairer and more structured results. System development followed the Rapid Application Development (RAD) methodology, which shortens planning, design, and implementation phases, while Laravel and MySQL were used as the core technologies. Testing results demonstrate that the system improves efficiency, accuracy, and transparency in the evaluation process. Consequently, the proposed system contributes to better decision-making and enhances the objectivity of HSE Awards implementation.